How motivation, opportunity, and ability drive knowledge sharing: The constraining‐factor model - Siemsen, Enno; Roth, Aleda V.; Balasubramanian, Sridhar (Journal of Operations Management, 2008)
AbstractWe introduce and empirically test a theoretical metamodel that explains knowledge‐sharing behavior among employees. Building on the well‐established motivation–opportunity–ability (MOA) framework, we posit that knowledge sharing among employees is a function of their MOA to do so. Existing literature suggests that the interaction among motivation, opportunity, and ability drives knowledge‐sharing behavior. In contrast, we specify a new model in which the “bottleneck” or constraining factor among the MOA variables determines the degree of knowledge sharing that occurs. This constraining‐factor model (CFM) fits the data better than the traditional multiplicative model and reveals a new, qualitatively different portrait of knowledge sharing that resolves some of the puzzles in the previous literature. The CFM provides macro‐level insights with respect to how operations managers can improve employee knowledge sharing by focusing on the bottleneck MOA variable. As a result, the CFM can help set strategic directions of related policies. The model emphasizes that, counter to conventional wisdom, the MOA variables should not be addressed independently, but rather in a dynamic and coordinated way.